2007
DOI: 10.3147/jsfp.42.219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Water Temperature on Betanodavirus Infection of Fingerling Humpback Grouper Cromileptes altivelis

Abstract: ABSTRACT-Fingerling humpback grouperCromileptes altivelis, experimentally infected with a betanodavirus (RGNNV genotype), were kept at 27∞C, 31∞C or 35∞C for 14 days. The numbers of dead fish in ten fish at each water temperature were five at 27∞C, two at 31∞C and one at 35∞C. The coat protein gene of the virus was detected by RT-PCR from four survivors at 27∞C, two survivors at 31∞C, but not from survivors at 35∞C. Histopathologically, vacuolation in the retinal tissues was observed in three survivors at 27∞C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
13
0
4
Order By: Relevance
“…The VNN-associated risk factors identified in this study included the temperature, DO, salinity, ammonia concentration in the water, fish size (adult > larvae), and life stage (age). Similarly, infection with the VNN virus has previously been shown to be influenced by host factors, such as age and environmental factors, particularly temperature [25]. Previous studies have shown that VNN first occurs from as early as 10 days post-hatching (dph) to 50 dph, and in some cases, fish beyond 50 dph in age can be affected, particularly strongly by the viral disease during periods of stress [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The VNN-associated risk factors identified in this study included the temperature, DO, salinity, ammonia concentration in the water, fish size (adult > larvae), and life stage (age). Similarly, infection with the VNN virus has previously been shown to be influenced by host factors, such as age and environmental factors, particularly temperature [25]. Previous studies have shown that VNN first occurs from as early as 10 days post-hatching (dph) to 50 dph, and in some cases, fish beyond 50 dph in age can be affected, particularly strongly by the viral disease during periods of stress [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Larval or juvenile stages are more prone to this viral infection, but significant mortality can also occur in older fish up to production-size as in European seabass, sevenband grouper, humpback grouper Cromileptes altivelis and Atlantic halibut Hippoglossus hippoglossus [4,37,71,83,86,125]. Infections are also reported in freshwater fish, such as Chinese catfish (P. asotus); Australia catfish (Tandanus tandanus); Barramundi (L. calcarifer); Medaka (Oryzias latipes); guppy (Poicelia reticulata) and zebrafish (Danio rerio) [5,22,52,53,62,63,76].…”
Section: Occurrence and Distributionmentioning
confidence: 99%
“…To control the infections, it is important to understand the epidemiology and pathogenic mechanisms of the virus. Betanodavirus infection can be influenced by host factors such as age [1,3], environmental factors such as water temperature [106,115,125] and other stress factors such as suboptimal feed, suboptimal water quality, crowding, transport and repeated spawning of broodstock [55,64,84,115]. The virus can be transmitted both horizontally [15,49,71,99] and vertically [2,7,14,49,83,84,92,102,119].…”
Section: Epidemiologymentioning
confidence: 99%
“…Selain itu, suhu air juga berpengaruh terhadap kelangsungan hidup virus VNN. Infeksi virus VNN di suhu perairan 27°C-31°C dilaporkan mampu menyebabkan kematian pada ikan kerapu bebek (Cromileptes altivelis), sedangkan peningkatan suhu di 35°C dapat menghambat perkembangbiakan virus VNN yang ditunjukkan dengan penurunan kematian ikan (Yuasa et al, 2007). Selanjutnya menurut Hata et al (2007)…”
Section: Hasil Dan Bahasanunclassified